Temporal Constructs and "Administrative Determinism": A Case Study from the Canadian Arctic - Halpern, Joel Martin; Christie, Laird (Anthropologica, 2022)
This paper considers time regulation as an aspect of Canadian governmental and institutional management of the lives of the Inuit. Utilizing data from the eastern Keewatin region it contrasts ’’land time" (literally time on the land, but also the traditional Inuit temporal orientation) with the chronometrically regulated time of the town. Its conclusions are twofold: time management is a part of a larger administrative design for the Inuit (and, parenthetically, indigenous peoples everywhere). This structuring of Inuit life around schools, jobs and government agencies cuts the Inuit off from the land and contributes to the severing of ties with their own past. Secondly, the paper offers the theoretical conclusion that for Sociology and Anthropology the study of time and temporal constructs provides an important and potentially rich field for research. In particular, the significance of the imposition of external temporal orders upon indigenous peoples has yet to be fully examined.